Transformation of Agrarian Law in the Digital Era: Implementation of Blockchain in Land Certification for Transparency and Prevention Dispute Agrarianism in Indonesia - Sunardi Sunardi; Tuti Nadhifah; Heni Risnawati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
Study This analyze adaptation system law Indonesian agrarian​ digital transformation, in particular implementation blockchain technology in certification land. Using approach juridical normative, research combining the statute approach with reviewing the UUPA, Regulation of the Minister of ATR/BPN Number 1 of 2021, and the ITE Law, as well as the conceptual approach that examines theory law agrarian, digital transformation, and principles Maqashid Syariah. Secondary data in the form of material primary, secondary, and tertiary law analyzed in a way descriptive qualitative For interpret the relationship between legal norms, theory and digital technology in land. Research results show that harmonization regulations agrarian and digital, blockchain implementation, and integration sharia principles can increase transparency, accountability, and certainty law. Digital transformation accelerates administration, minimizing overlapping overlap ownership, and strengthening governance fair and sustainable land. Research​ This confirm the need strengthening regulation, digital infrastructure, and literacy apparatus For support legal reform agrarian in the digital era.